SYNERGY BETWEEN STAKEHOLDERS IN WASTE MANAGEMENT PROGRAM THROUGH SIDARLING APPLICATION IN DENPASAR CITY - Faradiba Mauludia Agung, Magda (DIA: Jurnal Administrasi Publik, 2025)
The volume of waste in Denpasar City continues to increase yearly, and the amount of waste that is not handled is also relatively high. In accordance with the mandate of the Undang-Undang Nomor 18 Tahun 2008 concerning Waste Management and Derivative regulations have also been issued to strengthen the implementation of the law, namely Peraturan Pemerintah Nomor 27 Tahun 2020 concerning the Management of Specific Waste (such as hazardous and toxic waste, construction waste, medical waste, etc.), the Denpasar City Government made an innovation, namely a waste management program, through the SiDarling application. Researchers want to see how the synergy is built between stakeholders and how synergy is developed between stakeholders in waste management programs through the SiDarling application. Researchers will analyze stakeholders using the theory of Maryono et al., which classifies stakeholders into 3 (three), namely primary, secondary, and key stakeholders. The research method used is qualitative. The research results indicate that the SiDarling application’s potential to create synergy among waste management program stakeholders has not yet been completely realized, as seen from the lack of participation of society in the program. What becomes an obstacle is that communication and coordination with the society community are still ineffective even though socialization and education have been carried out, and this is felt to be less massive. With various existing problems, it is expected that the Denpasar City Government can evaluate the performance of the program in order to achieve the common goal of reducing the volume of waste in Denpasar City.